2022
DOI: 10.3389/fmars.2022.884262
|View full text |Cite|
|
Sign up to set email alerts
|

Methodologies for Patellid Limpets’ Aquaculture: From Broodstock Management to Juveniles

Abstract: The production of cultured limpets is a recent research field contributing to aquaculture diversification, focusing on low trophic species while reducing the carbon footprint. Limpets are gastropods that colonize rocky substrates and are mostly present on tidal and subtidal shores. This animal group is in high commercial demand and is endangered in several regions. The aquaculture production of limpets has been traditionally challenging. The most successful reproduction method has been gonadal dissection, as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(39 citation statements)
references
References 112 publications
9
30
0
Order By: Relevance
“…(Mau & Jha, 2018b; Nhan & Ako, 2014, 2016, 2019), Lottia sp. (Gould et al, 2001; Kay & Emlet, 2002; Nakano et al, 2020), Patella aspera (Castejón et al, 2021; Castejón, Nogueira, & Andrade, 2022), Patella caerulea (Ferranti et al, 2018), Patella ferruginea (Ferranti et al, 2022; Guallart et al, 2013; Guallart, Ferranti, et al, 2020; Guallart, Peña, et al, 2020), and also P. candei , with research focusing from larval production (Cañizares et al, 2021) to the settlement and management of the post‐larvae (Castejón, García, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…(Mau & Jha, 2018b; Nhan & Ako, 2014, 2016, 2019), Lottia sp. (Gould et al, 2001; Kay & Emlet, 2002; Nakano et al, 2020), Patella aspera (Castejón et al, 2021; Castejón, Nogueira, & Andrade, 2022), Patella caerulea (Ferranti et al, 2018), Patella ferruginea (Ferranti et al, 2022; Guallart et al, 2013; Guallart, Ferranti, et al, 2020; Guallart, Peña, et al, 2020), and also P. candei , with research focusing from larval production (Cañizares et al, 2021) to the settlement and management of the post‐larvae (Castejón, García, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the production of trochophores in limpets has been increased using alkaline baths to mature artificially the oocytes (Aquino De Souza et al, 2009; Castejón et al, 2021; Guallart, Peña, et al, 2020; Hodgson et al, 2007; Pérez et al, 2016; Wanninger et al, 1999; Wolfsohn, 1907). Cañizares et al (2021) showed that the production of trochophores in P. candei can be enhanced using NaOH baths at pH 9.0–9.5 for 2–3 h. Several studies also indicated that other alkaline agents like NH 4 OH can promote better larval production yields with significantly shorter bathing times (Castejón, García, et al, 2022; Gould et al, 2001; Hodgson et al, 2007; Nakano et al, 2020; Pérez et al, 2016; Ribeiro, 2008; Seabra et al, 2019; Wanninger et al, 1999). Another key factor for larval production is sperm density.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations